Mastering the model shoot : everything a photographer needs to know before, during, and after the shoot - Doorhof, Frank, 1971- (New Riders, 2014)
Doorhof takes you behind the scenes to reveal every step of his model-photography workflow. From finding models and locations and working with a team to indepth explanations of lighting setups, he shows you exactly how it's done, so you can recreate these same looks yourself.